Some Generalized Difference Sequence Spaces - Esi, A.; Isik, M. (Chiang Mai Univ, Fac Science, 2005)
The idea of difference sequences was introduced by Kizmaz [1]. In this paper, we define some new sequence spaces and give some topological properties of these new spaces. The results which we give in this paper are more general than those of Kizmaz [1], Et and Esi [3], Basarir [6] and Et et al.[2].
Keywords: Difference sequence spaces; paranorm